A Brief History of the Spy - Simpson, Paul, 1963- (London Constable & Robinson, 2013)
From the end of the Second World War to the present day, the world has changed immeasurably. The art of spying has changed too, as spies have reacted to changing threats. Here you will find the fascinating stories of real-life spies, both famous and obscure, from either side of the Iron Curtain, along with previously secret details of War on Terror operations. Detailed stories of individual spies are set in the context of the development of the major espionage agencies, interspersed with anecdotes of gadgets, trickery, honeytraps and assassinations worthy of any fictional spy. A closing
Include Index
Keywords: Spies -- Espionage -- Intelligence service